Acinar Adenocarcinoma of Prostate with Predominant Ttf-1 Positive Intraductal Component - Banu SARSIK; Nisar KARADENİZ; Adnan ŞİMŞİR; Rahmi AKYOL; Kutsal YÖRÜKOĞLU; Sait ŞEN (Federation of Turkish Pathology Societies, 2017)
Intraductal carcinoma of prostate has been previously described in radical prostatectomies. It's rarely encountered in needle biopsies in the absence of infiltrative carcinoma. But, both histogenesis and nomenclature of the lesion is still controversial. Among the pure intraductal carcinoma of prostate cases, a different solid patern was described with smaller nuclei at the center of the ducts. However, there is a lack of information about the association of those cases with acinar prostate adenocarcinoma. Herein, we describe a case of acinar adenocarcinoma with predominant non-neuroendocrine TTF-1 positive small cell intraductal component.